THE INFLUENCE OF PRODUCT EXCELLENCE AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT PT. BANK 9 JAMBI SUNGAI PENUH CITY BRANCH - Rahayu Putri, Veni; Yudesman, Yudesman; Ihsan Muarrif, Zul (Asian Journal of Islamic Economic Studies, 2024)
This study aims to determine the effect of product excellence and service quality on customer satisfaction at Bank 9 Jambi Sungai Penuh Branch. This research includes quantitative research, which can be interpreted as a method used to examine specific populations and samples. The number of samples used in this study was 30 people. The data in this study were obtained by distributing questionnaires or research questionnaires to customers at Bank 9 Jambi Sungai Penuh Branch. The results of this study indicate that product excellence and service quality have a positive and significant simultaneous (equally) effect on customer satisfaction at Bank 9 Jambi Branch Sungai Penuh. The findings partially show that product superiority has a positive and significant impact on customer satisfaction at Bank 9 Jambi Penuh Branch, and service quality has a positive and significant effect on customer satisfaction at Bank 9 Jambi Sungai Penuh Branch.